2022
DOI: 10.3390/jcdd9050126
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease with Mild and Mild to Moderate Reduction in Renal Function and Long-Term Recurrences of Atrial Fibrillation after Pulmonary Vein Cryoballoon Ablation

Abstract: The aim of this research was to evaluate if patients with chronic kidney disease (CKD) and mild or mild to moderate depression of renal function have an increased risk of atrial fibrillation (AF) recurrences after cryoballoon (CB) ablation. We performed a retrospective analysis of AF patients undergoing pulmonary vein isolation (PVI) by CB. The cohort was divided according to the KDIGO CKD-EPI classification into a (1) normal, (2) mildly decreased, or (3) mild to moderate reduction in estimated glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Yanagisawa et al 14) reported that a low estimated glomerular filtration rate at baseline was an independent predictor of recurrence after CBA in patients with PAF. Boriani et al 15) revealed that mild-to-moderate reductions in renal function was associated with a higher risk of AF recurrence after CBA. These results contradict the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yanagisawa et al 14) reported that a low estimated glomerular filtration rate at baseline was an independent predictor of recurrence after CBA in patients with PAF. Boriani et al 15) revealed that mild-to-moderate reductions in renal function was associated with a higher risk of AF recurrence after CBA. These results contradict the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A few reports have described the influence of impaired renal function on clinical outcomes in AF patients who underwent CBA. 14) 15) 16) However, the changes in renal function following CBA have not been fully elucidated. Thus, the purpose of this study was to compare the efficacy and safety of CBA in AF patients with CKD versus those without CKD and to evaluate the changes in renal function over 12 months after CBA in AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, predictors for these overall complications were coronary artery disease and peripheral artery disease, as well as age > 50 years, chronic kidney disease, hypertension and female gender [11,26,27]. Additionally, an analysis of the Nationwide Inpatient Sample (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) shows that obesity is an independent risk factor for immediate postablation complications and higher costs for patients undergoing catheter ablation for atrial fibrillation [28,29].…”
Section: Risk Factors For Vascular Complicationsmentioning
confidence: 99%
“…Patient comorbidities are a crucial aspect of ablation success, also in terms of clinical outcomes. A multicenter analysis of AF patients treated with cryoablation found that patients with chronic kidney disease, even with mild to moderate reduction in renal function, were associated with a higher risk of AF recurrences [ 60 ]. Conversely, the procedural success and complication rates were similar in patients with normal, mildly reduced, or mild to moderate reduction in glomerular filtration rate [ 60 ].…”
mentioning
confidence: 99%
“…A multicenter analysis of AF patients treated with cryoablation found that patients with chronic kidney disease, even with mild to moderate reduction in renal function, were associated with a higher risk of AF recurrences [ 60 ]. Conversely, the procedural success and complication rates were similar in patients with normal, mildly reduced, or mild to moderate reduction in glomerular filtration rate [ 60 ]. A case-control study showed that obese patients did not have higher AF recurrence rates after CA compared to patients with normal body weight, suggesting that body mass index alone may not be a criterion for refusing catheter ablation [ 61 ].…”
mentioning
confidence: 99%